The Effect of Coconut Water (Cocos nucifera L.) and Atonik to The Growth of Tomato Plant (Lycopersicum esculentum Mill.) - Intan Poespita Windiyani; Tundjung T. Handayani; Zulkifli Zulkifli; Bambang Irawan (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2020)
The purpose of this study was to find how the effects of coconut water plus atonic on tomato plant growth. The study was conducted from October to November 2019 at the Laboratory of Botany, Department of Biology FMIPA University of Lampung. The study was conducted in a 2x3 factorial experiment with a completely randomized design. Factor A is young coconut water with 3 levels of concentration i.e. 0% v/v, 25% v/v, and 50% v/v. Factor B is atonic with 2 concentration levels, namely 0% v/v and 10% v/v. As variables are high, fresh weight, dry weight, relative water content, and chlorophyll content of plants. Levene Test, Variance Analysis is carried out at a 5% significance level. Main effects and simple effects were analyzed by the Tukey test at 5% significance level. The results showed that the interaction between coconut water and atonic had a negative effect on the growth of tomato plants. The results of the study concluded that coconut water combine with atonic can not improve tomato plant growth.